2009
DOI: 10.1371/journal.pone.0005658
|View full text |Cite
|
Sign up to set email alerts
|

Full Factorial Analysis of Mammalian and Avian Influenza Polymerase Subunits Suggests a Role of an Efficient Polymerase for Virus Adaptation

Abstract: Amongst all the internal gene segments (PB2. PB1, PA, NP, M and NS), the avian PB1 segment is the only one which was reassorted into the human H2N2 and H3N2 pandemic strains. This suggests that the reassortment of polymerase subunit genes between mammalian and avian influenza viruses might play roles for interspecies transmission. To test this hypothesis, we tested the compatibility between PB2, PB1, PA and NP derived from a H5N1 virus and a mammalian H1N1 virus. All 16 possible combinations of avian-mammalian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
58
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 86 publications
5
58
0
Order By: Relevance
“…Briefly, the PB2, PB1, PA, and NP cDNAs of a highly pathogenic H5N1 virus, A/Vietnam/1203/04, were synthesized by reverse transcription of viral RNA and subcloned into the pHW2000 vector as described (27). In the RNP assay, pPOLI-NS-Luc was the reporter plasmid used for the determination of the viral polymerase activity (20). Expression of vRNA-like negative-sense luciferase RNA was driven by the polymerase I promoter.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, the PB2, PB1, PA, and NP cDNAs of a highly pathogenic H5N1 virus, A/Vietnam/1203/04, were synthesized by reverse transcription of viral RNA and subcloned into the pHW2000 vector as described (27). In the RNP assay, pPOLI-NS-Luc was the reporter plasmid used for the determination of the viral polymerase activity (20). Expression of vRNA-like negative-sense luciferase RNA was driven by the polymerase I promoter.…”
Section: Methodsmentioning
confidence: 99%
“…The plasmid pPOLI-NS-Luc that expresses vRNA-like luciferase RNA was used to monitor the activity of viral polymerases. If the RNP is functional, the vRNA produced from the pPOLI-NS-Luc plasmid will be transcribed by the viral polymerases leading to the synthesis of the luciferase protein used as a reporter (20). Human TLR10 expression plasmid was also cotransfected into 293T cells to examine the effect of its expression on viral replication as reflected in the luciferase activity.…”
Section: Tlr10 Is Expressed In Human Macrophages and Its Expression Ismentioning
confidence: 99%
“…Plasmids pCIPA, pCIPB1, and pCIPB2 expressing RNA polymerase subunits of influenza B/Panama/45/90 virus were described previously (15). Plasmid pPolI-Luc-RT for the generation of pPol-Luci-BNA-RT and pEGFP were kindly provided by L. L. M. Poon of the University of Hong Kong (18). The pPol-Luci-BNA-RT transcribes a viral RNA (vRNA)-like RNA, in which the noncoding sequences of influenza B NA segment flank the coding region of firefly luciferase.…”
Section: Methodsmentioning
confidence: 99%
“…Several pieces of evidence argue in favor of the selective advantage hypothesis. First, studies on the compatibility of polymerase proteins from human and avian influenza viruses showed that replacement of the human PB1 by its avian counterpart can enhance polymerase activity in minigenome reporter assays (13)(14)(15). Second, analyses of single-gene reassortants demonstrated an important role of the PB1 segment for the high virulence of the pandemic H1N1/1918 virus in mice and ferrets (16,17).…”
mentioning
confidence: 99%